Using exergame-based exercise to prevent and postpone the loss of muscle mass, muscle strength, cognition, and functional performance among elders in rural long-term care facilities: A protocol for a randomized controlled trial - Tuan, Sheng-Hui; Chang, Ling-Hui; Sun, Shu-Fen; Lin, Ko-Long; Tsai, Yi-Ju (Frontiers in Medicine, 2022)
Objective Elderly individuals in long-term care facilities (LTCFs) have a higher prevalence of sarcopenia than those in the community. Exercise is the gold standard for preventing and treating sarcopenia. Regarding exercise, multicomponent exercises, including progressive resistance training (PRT), are beneficial. However, developing routine, structured exercise programs for the elderly in LTCFs is difficult because of a shortage of healthcare providers, particularly in rural regions. Exergame-based exercises can increase a player’s motivation and reduce staff time for an intervention. Nintendo Switch RingFit Adventure (RFA) is a novel exergame that combines resistance, aerobic, and balance exercises. In this study, we aim to investigate the clinical effectiveness of RFA on muscle and functional performance parameters among the elderly in LTCFs. Methods The EXPPLORE (using EXergame to Prevent and Postpone the LOss of muscle mass, muscle strength, and functional performance in Rural Elders) trial is a single-center randomized controlled trial involving elderly individuals (≥60 years) living in LTCFs in rural southern Taiwan. The participants will be equally randomized to the intervention group (exergame-based exercise plus standard care) or the control group (standard care alone). Both groups will receive standard care except that the intervention group will receive exergame-based exercises at the time previously scheduled for sedentary activities in the LTCFs. The exergame-based exercise will be performed using RFA in the sitting position with a specialized design, including arm fit skills and knee assist mode. Each session of the exercise lasts 30 mins and will be performed two times per week for 12 weeks. The primary outcomes will be the osteoporotic fracture index, appendicular skeletal muscle mass index, dominant handgrip strength, and gait speed. Meanwhile, the secondary outcomes will be the dexterity and agility, muscle strength and thickness, range of motion of the joints of the dominant upper extremity, Kihon checklist, Medical Outcomes Study 36-Item Short-Form Health Survey, and Brain Health Test. Discussion This trial will provide valuable knowledge on whether exergames using RFA can counteract physical decline and improve quality of life and cognition among the elderly in LTCFs. Clinical trial registration [www.ClinicalTrials.gov], identifier [NCT05360667].